THE CONCEPT OF ENCOURAGEMENT AND ITS IMPORTANCE FOR LANGUAGE LEARNERS - Gulnora Sharapova (Modern American Journals, 2025)
Encouragement (*rag‘bat*) plays a fundamental role in the process of language acquisition by influencing learners' motivation, confidence, and persistence. This dissertation explores the concept of encouragement from a linguistic, psychological, and pedagogical perspective, analyzing how different forms of encouragement impact language learners. The study compares encouragement strategies in different educational settings and evaluates their effectiveness in second language acquisition (SLA). Using a mixed-methods approach, the research examines student and teacher perceptions, classroom interactions, and the role of sociocultural factors in shaping encouragement practices. The findings provide recommendations for educators to enhance student motivation and performance through effective encouragement strategies.
Keywords: Encouragement in education, Second language acquisition (SLA), Learner motivation, Language learning anxiety, Teacher-student interaction, Sociocultural factors in education, Positive reinforcement, Digital tools in language learning.